The Problems of Managing Tourism Business in Bangladesh: Causes and Remedial Measures - Tuli , Ferdouse Ara (Global Disclosure of Economics and Business, 2014)
Tourism Business is one of the fastest growing businesses in Bangladesh. It creates ample job opportunities for the unemployed people in Bangladesh. This business has been contributing remarkable to boost-up the economic development in Bangladesh. But the tourism business in Bangladesh has been suffering from the problems of effective management. Thus, this article aims to explore the causes of management problems facing the tourism business in Bangladesh. This article also attempts to provide the remedial measures to overcoming the existing management problems facing the tourism business in Bangladesh. JEL Classification Code: M 10; M 12; M 14